Evaluation of Cardiac Function in Pediatric Patients with Upper Airway Obstruction - Taliha Öner; Şehmuz Tekin; Zeynep Yıldız Yıldırmak; Berna Uslu Coşkun (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:Upper respiratory tract obstruction can cause cardiac and pulmonary dysfunction in children, which are largely reversible. We assessed the impact of upper respiratory tract obstruction on cardiac function in children scheduled for surgery for adenoidal and/or tonsillar hypertrophy.Methods:In total, 30 patients who were admitted to the ear nose and throat outpatient clinic and were scheduled for surgery for adenoidal and/or tonsillar hypertrophy and 30 control subjects were included into study. Peak nasal inspiratory flow (PNIF) was measured in all subjects, and echocardiographic and electrocardiographic examinations were performed.Results:The mean age of the patients was 9.43±2.51 years. The mean PNIF was significantly lower in patients (110.0 ± 43.9 L/min) than in the control group (140.7±39.4 L/min; p=0.006), and the mean P wave amplitude was significantly higher in patients than in controls (p<0.001). The mean pulmonary ejection time (ET) was significantly shorter in patients than in controls.Conclusion:Lower mean PNIF values in the patient group indicated increased airway resistance, suggesting that PNIF values below 110 L/min may affect right heart function. PNIF can be used by the pediatrician for screening to guide surgeons in children with adenoidal and/or tonsillar hypertrophy.